Calidad Microbiológica del Aire en la Vía de Evitamiento de Cajamarca 2020. - Muñoz-Borda, W. (2022)
It is a fact that microbiological air pollution is a serious problem for the world and increases year after year, which is why the objective was to analyze the microbiological quality of air associated with pollution where fungi and bacteria are present in the city of Cajamarca in the months of January and February, the data presented below determine that the microbiological quality is intermediate with an average of 412 CFU/m3. The monitoring area with the highest presence of microorganisms was point A. On the other hand, it was determined that the microbial concentrations were 412 CFU/m3 during the night, but point A recorded a higher presence with a high level of 906 CFU/m3. However, in Cajamarca fungal contamination was low with 75 CFU/m3 and bacterial contamination was moderate with 337 CFU/m3, identifying bacteria as: Staphylocacus Aureus, Staphylococcus Sp, Bacillus Subtilis, Streptococcus Sp and different fungi such as: Penicilliun Sp, Aspergillus and Fusarium, these being harmful to human health. Finally, we conclude that there is no direct relationship between the microbial concentration with humidity, temperature and vehicle traffic on the bypass road in Cajamarca, with the exception of point D, which indicates that there is a direct relationship between microbial concentrations with moisture.